Prevention Of Nutritional Disorders In Adolescent Girls - Kumari, Sushma (International Research Journal of Ayurveda & Yoga, 2021)
Adolescence is a transition period between childhood and adulthood characterized by puberty. It is a growth spurt in which an individual undergoes various physical, physiological, emotional and social changes. Therefore, nutritional needs are increased as compared to school years. An adolescent girl goes through a lot of changes which may lead to a number of disorders if unnoticed. For example, menstruation may lead to anaemia; hormonal changes may lead to obesity, infertility, PCOS, acne vulgaris and desire to be slim may lead to anorexia nervosa or bulimia & other problems like mood swings etc. In adolescent girls nutrition is of utmost importance because it will influence not only her own health but also health of the next generation (foetus) during reproduction period. Many other disorders like diabetes mellitus, dyslipidaemia, osteoporosis etc. may develop in later years. Such major health related problems can be prevented by few changes in lifestyle such as modifying dietary habits, intake of balanced diet, physical activities for digestion, absorption and assimilation of ingested food. These all are better described in Ayurveda. Details will be provided in paper.